Penerapan Recovery Experience dan Psychological Detachment untuk Mengurangi Work-Related Fatigue pada Karyawan Sektor Energi: Studi Kasus - Dila Arum Kusumastuti; M.G.Bagus Ani Putra (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Work-related fatigue is a condition resulting from the accumulation of prolonged job demands without adequate recovery processes. This condition may affect psychological well-being, sleep quality, emotional regulation, and work performance. This study aimed to examine the application of recovery experience and psychological detachment interventions in reducing work-related fatigue among employees in the energy sector. The study employed a Single Subject Research (SSR) approach using a single-case study design involving a 23-year-old female employee working as Health, Safety, Security, and Environment (HSSE) staff. Initial assessment using the Industrial Fatigue Research Committee (IFRC) indicated a high fatigue level with a score of 56. The DASS-42 results revealed mild depression (12), moderate anxiety (13), and severe stress (26). PAPI Kostick assessment showed a strong tendency toward achievement orientation, persistence in task completion, and high work commitment. The intervention consisted of three sessions focusing on recovery experience, psychological detachment, and emotional regulation. The intervention outcomes indicated positive changes, including improved awareness of recovery needs, implementation of sleep hygiene practices, reduced involvement in work activities during rest periods, increased engagement in recovery activities, and improved emotional awareness. These findings suggest that interventions based on recovery experience and psychological detachment may effectively reduce work-related fatigue among employees experiencing high job demands.